Evaluating the Aetiology of Tka Failure and Postoperative Function in Revision Knee Arthroplasty Patients - Imran Khan, Muhammad Inam, Hafiz Tayyab Irshad, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: This study investigates the aetiology of Total Knee Arthroplasty (TKA) failure and assesses the functional outcomes of patients undergoing revision Total Knee Arthroplasty (rTKA). Methods: A retrospective cohort study was conducted on 56 patients who underwent revision TKA due to failure of primary TKA. The study assessed the reasons for TKA failure, patient demographics, comorbidities, and preoperative and postoperative functional outcomes. Functional outcomes were measured using the Knee Society Score (KSS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Statistical analysis was performed to identify the factors associated with improved functional outcomes. Results: The most common reasons for TKA failure were aseptic loosening (42.9%), infection (21.4%), instability (17.9%), and polyethylene wear (10.7%). The average KSS improved from 42.3 to 79.4, and the average WOMAC score decreased from 53.2 to 21.3 following revision surgery. A significant correlation was found between the preoperative KSS and postoperative KSS (p<0.05). Conclusion: Aseptic loosening remains the leading cause of TKA failure. Revision TKA results in significant improvement in functional outcomes, although some patients still experience moderate functional deficits. Factors such as the patient's preoperative condition and comorbidities must be considered for improved postoperative success. Keywords: Total Knee Arthroplasty, Revision Total Knee Arthroplasty, TKA Failure, Functional Outcome, Knee Society Score, WOMAC, Aseptic Loosening, Infection, Instability, Polyethylene Wear.